Hayekian welfare states: Explaining the co-existence of economic freedom and big government - Andreas Bergh (Research Institute of Industrial Economics (IFN), 2018)
The idea that all types of economic freedom - including limited government - promote prosperity is challenged by the fact that some countries successfully combine a large public sector with high taxes and otherwise high levels of economic freedom. To explain the co-existence of economic freedom and big government, this paper distinguishes between big government in the fiscal sense of requiring high taxes, and in the Hayekian sense of requiring knowledge that is difficult to acquire by a central authority. The indicators of government size included in measures of economic freedom capture the fiscal size but ignore the Hayekian knowledge problem. Thinking about government size in both the fiscal and Hayekian dimensions suggests the possibility of Hayekian welfare states, where trust and state capacity facilitate experimentation and learning, resulting in a public sector that is big in a fiscal sense but not necessarily more vulnerable to the Hayekian knowledge problem. Pensions in Sweden are used as a case to illustrate the empirical relevance of the argument. The new pension system represents big government in a fiscal sense, but by relying on decentralized choice it requires relatively little central knowledge.
Keywords: H11; B25; 330; Welfare state; Hayek; Economic freedom; Economic reforms; State capacity